Molecular features of prenylated (iso)flavonoids from Fabaceae in relation to their potential NorA inhibition in Staphylococcus aureus - Irianti, Marina Ika; Ritsema, Janniek Henrieke; Hageman, Jos; Vincken, Jean-Paul; Araya-Cloutier, Carla (Frontiers in Pharmacology, 2026)
BackgroundThe overexpression of the NorA efflux pump is known to be an important factor in the antimicrobial resistance mechanism of Staphylococcus aureus. Therefore, NorA inhibition can help disarm this pathogen and tackle antimicrobial resistance. In this study, we aim to unravel the molecular properties of prenylated (iso)flavonoids from Fabaceae as potential NorA inhibitors and to propose leading compounds for future research.MethodsA collection of 37 prenylated isoflavonoids and flavonoids (obtained by purification, chemically synthesized, or commercially purchased), collectively referred to as (iso)flavonoids, was evaluated for its activity against norA-overexpressing Staphylococcus aureus using the checkerboard assay with ciprofloxacin (NorA substrate) and erythromycin (primarily non-NorA substrate), in combination with ethidium accumulation assays. Moreover, a norA-knockout Staphylococcus aureus strain was used to corroborate the specificity of the observed effects. Subsequently, in silico binary QSAR and pharmacophore models were developed to elucidate the key molecular properties for potential NorA inhibition.ResultsSeven prenylated (iso)flavonoids, namely, 8-prenylnaringenin, 6-C,7-O-diprenylnaringenin, glabrene, neobavaisoflavone, wighteone, licoisoflavone A, and glycyrrhisoflavone, potentiated ciprofloxacin up to 8-fold in norA-overexpressing and up to 2-fold in norA-knockout strains at 10 μM, without any membrane permeabilization effects. Moreover, prenylated (iso)flavonoids potentiated erythromycin in norA-overexpressing Staphylococcus aureus only up to 2-fold. Binary QSAR models were generated using datasets from the checkerboard and ethidium accumulation assays with a total prediction accuracy of up to 90% for active and 88% for inactive compounds. Based on QSAR models, the polar surface area, the balance of hydrophobicity and hydrophilicity, and the overall hydrophobicity were correlated with antibiotic potentiation and efflux inhibition of prenylated (iso)flavonoids. Moreover, in our study, we revealed that fractional negative polar surface area and formal (negative) charges are key properties that differentiate prenylated (iso)flavonoids with antimicrobial activity from those that act as potential NorA inhibitors. A pharmacophore model provided the basis for further optimization of prenylated (iso)flavonoids, mainly neobavaisoflavone and wighteone, as potential NorA inhibitors.ConclusionIn our study, we provide, for the first time, predictive QSAR models of prenylated (iso)flavonoids as potential NorA inhibitors and propose two potential leads based on this family of plant-derived compounds. Future research on the specificity and validation of prenylated (iso)flavonoids as NorA inhibitors is required.